HIV-specific CAR T cells return to the clinic - Christopher W. Peterson (The Journal of Clinical Investigation, 2021)
Over the past decade, chimeric antigen receptor (CAR) T cells have emerged as the prototype gene therapy for B cell leukemias. These so-called living drugs are derived from a patient’s own cells, reprogrammed to recognize and destroy cancer cells, and then reintroduced into the body. The huge success of this therapy for cancer is rooted in pioneering clinical and preclinical studies, established more than three decades ago, focused on persistent HIV-1 infection. In this issue of the JCI, Bingfeng Liu et al. revisit HIV-specific CAR T cells in an important clinical study that supports broader application of this groundbreaking therapy. Although curative endpoints were not achieved, these findings lay the foundation for augmented approaches applying combinatorial technologies including antigen supplementation.